The constructivist view in science education – what it has to offer and what should not be expected from it - Duit, Reinders (Investigações em Ensino de Ciências, 1996)
There is certainly something fashionable about constructivism in science education nowadays. It is further true that constructivism is by no means a consistent movement, there are many variants of this view in use. Furthermore, it appears that constructivism, for some science educators, in any case, has become the new ideology of science education that provides a cure for every problem of teaching and learning science. But without any doubt constructivism has become also a most valuable guideline for science education – for science teaching and learning as well as for research in these fields. This paper attempts to review the myths, the misunderstandings, the polemics and the serious critiques concerning constructivism. It will be argued in favor of a consistent and "moderate" constructivist view in science education that in fact may provide substantial progress in our field and which major features will be among the valuable views of science education even after the term constructivism will have gone out of fashion.